If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = -2 + k Solving 7 = -2 + k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-1k' to each side of the equation. 7 + -1k = -2 + k + -1k Combine like terms: k + -1k = 0 7 + -1k = -2 + 0 7 + -1k = -2 Add '-7' to each side of the equation. 7 + -7 + -1k = -2 + -7 Combine like terms: 7 + -7 = 0 0 + -1k = -2 + -7 -1k = -2 + -7 Combine like terms: -2 + -7 = -9 -1k = -9 Divide each side by '-1'. k = 9 Simplifying k = 9
| 88x-123=90 | | x(2x+1)(x-2)(x+2)=0 | | 3y-3=4y-8 | | 50x^5/18x | | q+45=-5 | | 4x^2-6x+3=-15 | | 5y-8=8y-5 | | -72+22y=-6 | | 12x+6=2x | | t^2-16/(t^2)^2 | | m^2-.5m=3.5 | | -72+4y+6y=-6 | | f(x)=5cosx+8 | | ln(2x-5)=2 | | 276/8=203/4+v | | x^2+3.5x=7 | | 6/17=-54/x | | (1+v)(3v-2)=0 | | 5t-6=3-4t | | -9(-9)-7y=63 | | 5x-9=35(x-2) | | -3(1-x)=2(x+1) | | 8-x=x-1 | | -9(1)-7y=63 | | x^2-5.5x-.5=0 | | -9*(1)-7y=63 | | x^2-7x+6=(x-1)(ax+b) | | a(n)=3+2(n-1) | | x^2-11/2x-1/2=0 | | 2(x-1)=-3(x+3) | | (3x-2)3=0 | | 17x-27=30x-94 |